Pemberdayaan Barang Milik Negara : Optimalisasi Pencapaian Kinerja Berbasis Competitive Advantage - Trisdaningrum, Rinda; Ardini, Lilis; Handayani, Nur (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2024)
The property is also one of the state assets that functions to increase government service quality and quantity to the public. It can be optimized to increase the state revenue. Moreover, the population was the work unit of the area office of the Ministry of Law and Human Rights in East Java province. The location was in the Surabaya area coordinator. This study aimed to find out and provide options for empowering state property to optimize performance achievements based on competitive advantage possessed by using Resource Based View analysis. The data were primary, taken from the interviews, and secondary data of state property management. As a result, it showed that there was still a lack of management of state property in Surabaya area coordinator. This happened as there had not been optimal yet non-tax revenue from its management because of unsupporting factors. Additionally, the Resource Based View approach was used to analyze VRIO (Valuable, Rare, Inimitable, Organization) characteristics as a proper strategy for improving the organization's internal resource capacity, such as fixed assets, human resources, and organization to determine competitiveness for the organization.